Effects of pulmonary rehabilitation on respiratory function in mechanically ventilated patients: a systematic review and meta-analysis - Xiong Xingyu; Zhang Dandan; Cheng Shouzhen (BMC Pulmonary Medicine)
Abstract Aim The aim of this systematic review and meta-analysis was to explore the effects of different pulmonary rehabilitation on respiratory function in mechanically ventilated patients and to determine the optimal type of intervention. Method A comprehensive search was conducted using PubMed, Embase, Web of Science, Joanna Briggs Institute(JBI), and the Cochrane Library from their inception until September 16th, 2024. The search targeted randomized controlled trials (RCTs) comparing pulmonary rehabilitation or usual care, for improving respiratory function in mechanically ventilated patients. We performed a meta-analysis utilizing Endnote X9 and R 4.3.1. Results Twelve articles were included for systematic review and ten articles were analyzed in the meta-analysis.The primary outcomes such as Maximum inspiratory pressure(MIP)[n = 10 studies, sample size 216 (intervention) vs. 218 (control), MD = 7.45, 95% CI: 3.81 to 11.09], Maximum expiratory pressure(MEP)[n = 5 studies, sample size 115 (intervention) vs. 112 (control), MD = 13.98, 95% CI:7.41 to 20.54], Rapid shallow breathing index(RSBI)[n = 4 studies, sample size 96 (intervention) vs. 98 (control), MD = -33.85, 95% CI:-71.18 to 3.48] and Tidal volume(VT)[n = 4 studies, sample size 96 (intervention) vs. 98 (control), MD = 74.64, 95% CI:21.7 to 127.57] shows that MIP, MEP and VT significantly improved after the pulmonary rehabilitation.The random-effects models were employed because of the modest degree of heterogeneity present. Conclusion Pulmonary rehabilitation showed mixed effects on significantly improved the MIP, MEP, VT and DT. Pulmonary rehabilitation by inspiratory muscle training could administer the best therapeutic effect, followed by neuromuscular electrical stimulation. Clinical trial number Not applicable.